Glucose Metabolism as a Pre-clinical Biomarker for the Golden Retriever Model of Duchenne Muscular Dystrophy - Schneider, Sarah Morar (Mol Imaging Biol, 2018)
PURPOSE: Metabolic dysfunction in Duchenne muscular dystrophy (DMD) is characterized by reduced glycolytic and oxidative enzymes, decreased and abnormal mitochondria, decreased ATP, and increased oxidative stress. We analyzed glucose metabolism as a potential disease biomarker in the genetically homologous golden retriever muscular dystrophy (GRMD) dog with molecular, biochemical, and in vivo imaging. PROCEDURES: Pelvic limb skeletal muscle and left ventricle tissue from the heart were analyzed by mRNA profiling, qPCR, western blotting, and immunofluorescence microscopy for the primary glucose transporter (GLUT4). Physiologic glucose handling was measured by fasting glucose tolerance test (GTT), insulin levels, and skeletal and cardiac positron emission tomography/X-ray computed tomography (PET/CT) using the glucose analog 2-deoxy-2-[(18)F]fluoro-d-glucose ([(18)F]FDG). RESULTS: MRNA profiles showed decreased GLUT4 in the cranial sartorius (CS), vastus lateralis (VL), and long digital extensor (LDE) of GRMD vs. normal dogs. QPCR confirmed GLUT4 downregulation but increased hexokinase-1. GLUT4 protein levels were not different in the CS, VL, or left ventricle but increased in the LDE of GRMD vs. normal. Microscopy revealed diffuse membrane expression of GLUT4 in GRMD skeletal but not cardiac muscle. GTT showed higher basal glucose and insulin in GRMD but rapid tissue glucose uptake at 5 min post-dextrose injection in GRMD vs. normal/carrier dogs. PET/ CT with [(18)F]FDG and simultaneous insulin stimulation showed a significant increase (p = 0.03) in mean standard uptake values (SUV) in GRMD skeletal muscle but not pelvic fat at 5 min post-[(18)F]FDG /insulin injection. Conversely, mean cardiac SUV was lower in GRMD than carrier/normal (p < 0.01). CONCLUSIONS: Altered glucose metabolism in skeletal and cardiac muscle of GRMD dogs can be monitored with molecular, biochemical, and in vivo imaging studies and potentially utilized as a biomarker for disease progression and therapeutic response. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11307-018-1174-2) contains supplementary material, which is available to authorized users.